First- and Third-Person Perspectives in Immersive Virtual Environments: Presence and Performance Analysis of Embodied Users - Gorisse, Geoffrey; Christmann, Olivier; Amato, Etienne Armand; Richir, Simon (Frontiers in Robotics and AI, 2017)
Current design of virtual reality (VR) applications relies essentially on the transposition of users' viewpoint in first-person perspective (1PP). Within this context, our research aims to compare the impact and the potentialities enabled via the integration of the third-person perspective (3PP) in immersive virtual environments (IVE). Our empirical study is conducted in order to assess the sense of presence, the sense of embodiment and performance of users confronted with a series of tasks presenting a case of potential use for the video game industry. Our results do not reveal significant differences concerning the sense of spatial presence with either point of view. Nonetheless, they provide evidence confirming the relevance of using the first-person perspective to induce a sense of embodiment toward a virtual body, especially in terms of self-location and ownership. However, no significant differences were observed concerning the sense of agency. Concerning users' performance, our results demonstrate that the first-person perspective enables more accurate interactions, while the third-person perspective provides better space awareness.